Selective Persulfide Detection Reveals Evolutionarily Conserved Antiaging Effects of S-Sulfhydration - Zivanovic, Jasmina; Kouroussis, Emilia; Kohl, Joshua B.; Adhikari, Bikash; Bursac, Biljana; Schott-Roux, Sonia; Petrovic, Dunja; Miljkovic, Jan Lj; Thomas-Lopez, Daniel; Jung, Youngeun; Miler, Marko; Mitchell, Sarah; et al. (Cell metabolism, 2019)
Life on Earth emerged in a hydrogen sulfide (H2S)-rich environment eons ago and with it protein persulfidation mediated by H2S evolved as a signaling mechanism. Protein persulfidation (S-sulfhydration) is a post-translational modification of reactive cysteine residues, which modulate protein structure and/or function. Persulfides are difficult to label and study due to their reactivity and similarity with cysteine. Here, we report a facile strategy for chemoselective persulfide bioconjugation using dimedone-based probes, to achieve highly selective, rapid, and robust persulfide labeling in biological samples with broad utility. Using this method, we show persulfidation is an evolutionarily conserved modification and waves of persulfidation are employed by cells to resolve sulfenylation and prevent irreversible cysteine overoxidation preserving protein function. We report an age-associated decline in persulfidation that is conserved across evolutionary boundaries. Accordingly, dietary or pharmacological interventions to increase persulfidation associate with increased longevity and improved capacity to cope with stress stimuli. [Display omitted] •Dimedone Switch method is a versatile, chemoselective persulfide labeling approach•Protein persulfidation is an evolutionarily conserved modification of cysteine thiols•Persulfidation waves rescue cysteines from overoxidation caused by ROS•Persulfidation decreases with aging, increases with caloric restriction, and extends lifespan Zivanovic et al. develop a robust method for chemoselective persulfide labeling using dimedone-based probes to show that persulfidation is an evolutionarily conserved post-translational modification used by the cells to protect proteins from overoxidation caused by different stressors. Higher persulfidation levels, caused by pharmacological or dietary interventions, lead to better resistance to oxidative stress and longer life.